Effect of a mutation in Raffinose Synthase 2 (GmRS2 ) on soybean quality traits - Silva,Luiz Cláudio Costa (2019)
Abstract The presence of stachyose and raffinose is considered an antinutritional factor for humans and monogastric animals, leading to limitations on soybean consumption as a protein source. In the present study, the effect of a mutation in the raffinose synthase 2 gene was measured on soybean quality traits. We used an F2 population with 168 soybean individuals developed by crossing four soybean lines and evaluated oil, protein, sucrose, raffinose, stachyose and fatty acid contents and their relationships. The mutation explained 69.61%, 51.81% and 31.96% of stachyose, raffinose and sucrose variation, respectively, and we were able to produce soybean with average stachyose of 0.18%. The low coefficients of determination for protein and oil indicate that the mutation can be used to increase sucrose and reduce raffinose and stachyose content without major changes in oil and protein.